Commentary on "Evaluating service users' experiences of using Talking Mats®". Issue 2 (3rd April 2018) - Harding, Celia; Stewart, Alison
Abstract : Purpose: The purpose of this paper is to provide some thoughts following on from reading "Evaluating service users' experiences of using Talking Mats®". Design/methodology/approach: This commentary outlines some considerations for the continued discussions about how to engage people who have profound and multiple learning disabilities. Findings: The literature is not clear on the involvement of people with more profound and multiple learning disabilities, or for those who do not use much spoken language. Some papers have explored the notions of involvement and interpretation of pre-intentional communicators' desires and interests. Originality/value: There needs to be a robust discussion across carer, academic and service user communities to consider what the communication rights and needs are for people who have profound and multiple disabilities.